Associations between dietary indices and hearing status among middle-older aged adults - results from the Baltimore Longitudinal Study of Aging - Jin, Yichen; Tanaka, Toshiko; Reed, Nicholas S; Tucker, Katherine L; Ferrucci, Luigi; Talegawkar, Sameera A (The American journal of clinical nutrition, 2024)
Hearing loss, a public health issue in older populations, is closely related to functional decline. To investigate the longitudinal associations between 4 dietary indices and hearing status. Data from the Baltimore Longitudinal Study of Aging were used and included 882 participants ≥45 y of age. Dietary intake was assessed using a validated food frequency questionnaire, and 4 dietary scores (Mediterranean-Dietary Approaches to Stop Hypertension Intervention for Neurodegenerative Delay diet [MIND], Mediterranean style diet score [MDS], Alternative Healthy Eating Index [AHEI], and Healthy Eating Index [HEI]) were calculated as averages over time. Hearing status was examined using pure-tone audiometry, and pure-tone average (PTA) of hearing thresholds were calculated at speech-level (PTA ), low (PTA ), and high (PTA ) frequencies, with lower thresholds indicating better hearing. Multivariable linear mixed-effect models were used to examine associations between dietary indices and hearing threshold change over time adjusted for confounders. At baseline, the mean age of participants was 67 y and 55% were female. Over a median of 8 y of follow-up, MDS ≥7 was associated with 3.5 (95% CI: -6.5, -0.4) and 5.0 (95% CI: -9.1, -1.0) dB lower PTA and PTA , respectively, compared with MDS ≤3; the highest tertile of the AHEI was associated with 2.3 (95% CI: -4.6, -0.1) and 5.0 (95% CI: -8.0, -2.0) dB lower PTA and PTA ; and each standard deviation increment in HEI was associated with 1.6 dB (95% CI: -2.7, -0.6), 1.1 dB (95% CI: -2.1, -0.1), and 2.1 dB (95% CI: -3.5, -0.6) lower PTA , PTA , and PTA , respectively. Adherence to healthy dietary patterns was associated with better hearing status, with stronger associations at high frequencies. Am J Clin Nutr 20xx;x:xx.